The Relationship Between Respiration Rate and Quality Parameters of Russet Potatoes During Long-Term Storage - Pedrosa, Vanessa Maria Dantas [UNESP]; Izidoro, Maiqui [UNESP]; Paythosh, Samuel; Dungan, Robert S.; Olsen, Nora; Spear, Rhett; de Almeida Teixeira, Gustavo Henrique (Springer Nature, 2025)
Understanding the storage requirements of emerging potato cultivars is paramount for effective storage management. Thus, the objective of this study was to quantify the respiration rates of the standard Russet Burbank, and the new cultivars Ivory Russet, Dakota Russet, and Rainier Russet potatoes to understand the relationship between respiration rate and quality parameters during storage. Tubers were cured at 12.8 °C and 95% relative humidity (RH) for 14 days before gradually transitioning to 5.5, 7.2, or 8.9 °C (95% RH). Lower respiration rates were observed at 5.5 °C, with comparable rates at 7.2–8.9 °C. Dakota Russet had lower respiration rates (0.95 mg CO2 kg−1 h−1) while Rainier Russet the highest (1.29 mg CO2 kg−1 h−1). Sucrose content was negatively affected by respiration of Ivory Russet, Rainier Russet, and Russet Burbank, glucose content was affected by all cultivars, though. Fry color (Photovolt reflectance) was positively correlated to the respiration rates of all cultivars. The respiration rates had low correlations with all quality parameters.
Keywords: Fry color; Processing; Solanum tuberosumL; Sugars; Temperature